Developing library and information center collections - Evans, G. Edward 1937-; Saponaro, Margaret Zarnosky (Libraries Unlimited, 2005)
This latest edition continues to cover all phases of collection development―from needs assessment, policies, and the selection process (theory and practice), to publishers, serials, protection, legal issues, censorship, and intellectual freedom. Each chapter has been extensively revised to reflect changing practices, policies, and technologies. To this end, some chapters―electronic materials, government information, audiovisual materials, and resource sharing―have been almost completely rewritten. In addition, electronic serials, introduced in the 4th edition, has been combined with its print counterpart in a single chapter. New to this edition is a CD containing supplementary material; a companion Web site () will also be maintained to ensure URLs referenced throughout the text are kept up to date. As the authors put it in their introductory chapter, whatever environment one works in, collection development is an exciting challenge that requires lifelong learning. Students and practitioners alike will benefit greatly from this state-of-the-art text.--Provided by publisher.